Three Types of Isocoumarins with Unusual Carbon Skeletons from Artemisia dubia var. subdigitata and Their Antihepatoma Activity - Yang, Ke‐Xin; Li, Tian‐Ze; Ma, Yun‐Bao; Wang, Yong‐Cui; Li, Feng‐Jiao; Chen, Ji‐Jun (Chinese journal of chemistry, 2024)
Comprehensive Summary Ten novel isocoumarins, including four pairs of enantiomers, were isolated from Artemisia dubia var. subdigitata (Asteraceae). Compounds 1, 2 and 3a/3b possessed a unique 6/6/6‐tricyclic system comprising an unusual 1‐(2‐methylcyclohexyl) propan‐1‐one moiety fused with isocoumarin core skeleton. Compounds 4a/4b were characterized as an unexpected 2,5‐dimethylcyclohexan‐1‐one scaffold, and compounds 5a/5b and 6a/6b were rare 1,2‐seco‐isocoumarin. Their structures and absolute configurations were elucidated through spectroscopic data, X‐ray crystallography, ECD and NMR calculations with DP4+ analyses. Plausible biosynthetic pathways were proposed from the naturally occurring isocoumarin. Network pharmacological analysis suggested that the targets of compound 1 were significantly enriched in the cell cycle and PI3K‐Akt signaling pathway. The molecular docking revealed that compound 1 had high binding affinity with CDK2 (total score: 6.8717). Furthermore, compounds 1 and 2 exhibited inhibitory activity on three human hepatoma cell lines, with inhibitory ratios of 85.1% and 84.5% (HepG2), 88.2% and 87.3% (Huh7), and 69.2% and 69.1% (SK‐Hep‐1) at 200 μmol·L–1, respectively. Artemdubones A—F (1—6) were isolated from Artemisia dubia var. subdigitata. Compounds 1, 2 and 3a/3b possessed a unique 6/6/6‐tricyclic system comprising an unusual 1‐(2‐methylcyclohexyl) propan‐1‐one moiety fused with isocoumarin core skeleton. Compounds 4a/4b were characterized as an unexpected 2,5‐dimethylcyclohexan‐1‐one scaffold, and compounds 5a/5b and 6a/6b were rare 1,2‐seco‐isocoumarin